A community built on words the constitution in history and politics - Powell, Jefferson, 1954- (Chicago, [Ill.] : University of Chicago Press, 2002)
Combining history and theory, Powell analyzes a series of constitutional controversies from 1790 to 1944 to demonstrate that constitutional law from its very beginning has involved politically charged and ideologically divisive arguments. Nowhere in America's past can one find the golden age of apolitical constitutional thinking that a great deal of contemporary scholarship seeks or presupposes. Viewed over time, American constitutional law is a history of political dispute couched in constitutional terms.
Specialized.
Description based on print version record.
Includes index.
Keywords: Constitutional law -- United States; Constitutional history -- United States; United States -- Politics and government; Law; United States of America, USA; 18th century, c 1700 to c 1799.; 19th century, c 1800 to c 1899.; 20th century, c 1900 to c 1999.; History: specific events & topics